PENDEKATAN PEMBELAJARAN STUDENT CENTERED LEARNING PADA LAGU INDONESIA RAYA DI EKSTRAKURIKULER PADUAN SUARA SMPN 2 GRESIK - adawiyah; senyum Sadhana (Universitas Negeri Surabaya, 2026)
Vokal adalah sumber suara yang berasal dari pita suara, dengan berbagai karakteristik. Setiap individu memiliki karakter suara dan ciri khas yang berbeda-beda. Suara yang dihasilkan dapat dipetakan atau dipecah menjadi soprano, alto, tenor, dan bass. Kelompok vokal yang menekan kerja kelompok untuk menciptakan harmoni yang terpadu disebut paduan suara. Paduan suara adalah ansambel musik yang terdiri dari sekelompok penyanyi yang menyanyikan lagu bersama secara harmonis. Kelompok yang dimaksud menggabungkan berbagai jenis suara, umumnya soprano, alto, tenor, dan bass. This study aims to describe the process and implementation of a student-centered approach in teaching the Indonesian national anthem (Indonesia Raya) in the choir extracurricular activities at SMP Negeri 2 Gresik. The study used a qualitative approach with a case study design. Participants were selected purposively, consisting of student choir members, coaches, and activity coordinators. Data collection was conducted through participant observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. This study shows that the student-centered approach works through three main phases: planning independent practice, exploring digital learning resources, and group reflection facilitated by a coach as a mentor. In this context, students not only develop technical vocal competencies such as intonation, articulation, and harmony, but also develop independent learning, collective responsibility, and internalize national values ​​through shared aesthetic experiences. The song Indonesia Raya serves as an affective medium that strengthens national identity and group cohesion. The results of this study conclude that the student-centered approach in arts extracurricular activities has proven effective as a contextual response to the limited time and personnel of specialist educators, while also being relevant to the spirit of the Independent Curriculum, which emphasizes participatory and meaningful learning.